2001
DOI: 10.1002/1521-3773(20010817)40:16<3062::aid-anie3062>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous One-Pot Synthesis of Derivatized Cyclopentadienyl-Tricarbonyl Complexes of99mTc with an In Situ CO Source: Application to a Serotonergic Receptor Ligand

Abstract: Instant radiopharmaceuticals—just add [99mTcO4]− in water! Half‐sandwich complexes of the type [(RCOCp)99mTc(CO)3] (e.g. 1) were synthesized in a single step in water from [99mTcO4]−. The acidification of the Cp ring by a carbonyl substituent and the use of K2[H3BCO2] as a reducing agent and in situ source of CO are instrumental in the synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 31 publications
1
77
0
Order By: Relevance
“…In which concerns the development of 99m Tc-based imaging agents selective for CNS receptors, [ 99m Tc]TRO-DAT-1 represents up to now the most successful development for imaging DAT sites [3]. Since the introduction of the low-valent aquo-carbonyl complex fac-[ 99m Tc(OH 2 ) 3 (CO) 3 ] + as a versatile precursor for the labelling of biomolecules, a number of biologically active peptides and CNS receptor ligands have been labelled making use of different bifunctional chelating agents (BFCA) [4][5][6][7][8][9][10][11][12][13][14][15]. Despite the recent advances in this area, further achievements still rely on the development of new 99m Tc-organometallic complexes with adequate in vitro and in vivo behaviour, in order to obtain radiopharmaceuticals that fulfil the minimum requisites for CNS receptor imaging.…”
Section: Introductionmentioning
confidence: 99%
“…In which concerns the development of 99m Tc-based imaging agents selective for CNS receptors, [ 99m Tc]TRO-DAT-1 represents up to now the most successful development for imaging DAT sites [3]. Since the introduction of the low-valent aquo-carbonyl complex fac-[ 99m Tc(OH 2 ) 3 (CO) 3 ] + as a versatile precursor for the labelling of biomolecules, a number of biologically active peptides and CNS receptor ligands have been labelled making use of different bifunctional chelating agents (BFCA) [4][5][6][7][8][9][10][11][12][13][14][15]. Despite the recent advances in this area, further achievements still rely on the development of new 99m Tc-organometallic complexes with adequate in vitro and in vivo behaviour, in order to obtain radiopharmaceuticals that fulfil the minimum requisites for CNS receptor imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Some successful approaches to [Cp 99m Tc(CO) 3 ] have been reported but they suffer from harsh conditions and the need for organic solvents [53,54]. We assumed that lowering the pK a value would lead to more facile deprotonation with the negatively charged cyclopentadienyl ligand be more prone for coordination, a hypothesis that turned out to be correct [55]. Introducing an acetyl group in cyclopentadien lowered the pK a value to around 8.7 as determined by simple potentiometric pH titration and provided increased water solubility and stability to the ligand.…”
Section: The Cp Problem -Formation Of Further M-c Bonds In Watermentioning
confidence: 99%
“…ACp was described in the early literature but the pK a was not determined. Later, it was found that the pK a value of Acp was around 8.7 [86]. Acp is water-soluble and reasonably stable.…”
Section: Reaction With Nonclassical Ligandsmentioning
confidence: 99%
“…In general, the conditions worked out so far in the context suffer from rather rough conditions and are, in general, not compatible with demands from routine application. The only exception is probably the labelling of ACp derivatives of biomolecules which can be performed directly in water although the concentrations of biomolecules are still relatively high [86]. 188 3 ] for the labelling of biomolecules such as peptides or proteins.…”
Section: Cns Receptor Ligandsmentioning
confidence: 99%